The global public management revolution - Kettl, Donald F. (Brookings Institution Press, 2005)
"Explores the current models of government reform across the world, examining the basic tool kit of reformers and probing the underlying issues of government management and the puzzles of governance in the twenty-first century, with special focus on New Zealand and the United States"--Provided by publisher